Роль качественных методов в исследовании социальных конфликтов - Даниленко, О. (Социология: теория, методы, маркетинг, 2006)
Conjoint solution of measuring methodological problems by conflictology and qualitative sociology are grounded in the article. Particular significance of text information
in conflictological interpretation practice is proved with reference to measuring of
conflictness peculiarities analysis concerning on each of the main strategies of qualitative research (case study, grounded theory, biographic method, oral history and
ethnographic research). New techniques of conflictological expertise designed on the
base of linguo conflictological approach to socio communicative processes research
are proposed. Research methodology of conflict meta language construction and
expediency of one are grounded. Narrative conflictological content analysis methodology with reference to identities measuring (including processes of new identities
forming and revealing their conflict potential) is also grounded and expediency of one
is substantiated.